2015
DOI: 10.1016/j.surg.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion is associated with increased risk of perioperative complications and prolonged hospital duration of stay among patients undergoing amputation

Abstract: Among patients who had major lower-extremity amputation, perioperative transfusion independently predicted greater risks for perioperative pneumonia, thromboembolism, and prolonged hospital DOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 54 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…1416,32 The large number of CLTI patients with anemia highlights the need for clinical practice guidelines, yet recommendations from vascular societies currently do not exist. Our observations reflect the lack of a uniform standard to guide the appropriateness of blood product usage, as hematocrit values that triggered transfusions varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…1416,32 The large number of CLTI patients with anemia highlights the need for clinical practice guidelines, yet recommendations from vascular societies currently do not exist. Our observations reflect the lack of a uniform standard to guide the appropriateness of blood product usage, as hematocrit values that triggered transfusions varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…22 On the other hand, the presence of anemia associated with blood transfusions in patients who undergo amputation is also considered a negative prognostic factor for occurrence of complications such as pneumonia, venous thromboembolism, and prolonged hospital stay. 23 In diabetics, local infections, with plantar ulcers, edema, and hyperemia, are known high-risk factors for amputations. 8,24 However, the present study observed that only sepsis was related to major amputations, irrespective of the presence of local infection.…”
Section: 15mentioning
confidence: 99%
“…Nonetheless, our finding of increased complications in those receiving preoperative transfusion is consistent with observations reported by other authors. 4,8,9,18,19 …”
Section: Discussionmentioning
confidence: 99%